Mastering Ethereum : building smart contracts and DApps - Antonopoulos, Andreas M.; Wood, Gavin, Dr. (Mumbai : Shroff Publishers, 2019)
Ethereum represents the gateway to a worldwide, decentralized computing paradigm. This platform enables you to run decentralized applications (DApps) and smart contracts that have no central points of failure or control, integrate with a payment network, and operate on an open blockchain. With this practical guide, Andreas M. Antonopoulos and Gavin Wood provide everything you need to know about building smart contracts and DApps on Ethereum and other virtual-machine blockchains. Discover why IBM, Microsoft, NASDAQ, and hundreds of other organizations are experimenting with Ethereum. This essential guide shows you how to develop the skills necessary to be an innovator in this growing and exciting new industry.
What is Ethereum? -- Ethereum basics -- Ethereum clients -- Cryptography -- Wallets -- Transactions -- Smart contracts and solidity -- Smart contracts and Vyper -- Smart contract security -- Tokens -- Oracles -- Decentralized applications (DApps) -- The Ethereum Virtual Machine [EVM] -- Consensus -- Ethereum fork history -- Ethereum standards -- Ethereum EVM opcodes and gas consumption -- Development tools, frameworks, and libraries -- web3.js tutorial -- Short links reference.
Includes index.
CSE
Keywords: Blockchains (Databases).; Virtual computer systems; Web applications -- Programming; Computer science; Cloud Computing